Medication self-management toolkits for adults with multiple sclerosis: A scoping review - Sara J.T. Guilcher; Lauren Cadel; Andrea He; Stephanie R. Cimino; Maham Ahmed; Chester H. Ho; Sander L. Hitzig; Lisa M. McCarthy; Tejal Patel; Shoshana Hahn-Goldberg; Aisha K. Lofters; Tanya L. Packer (Elsevier, 2023)
Background: Multiple sclerosis (MS) is an autoimmune disease that is often treated with multiple medications. Managing multiple medications, also known as polypharmacy, can be challenging for persons with MS. Toolkits are instructional resources designed to promote behaviour change. Toolkits may support medication self-management for adults with MS, as they have been useful in other populations with chronic conditions. Objective: The main purpose of this review was to identify and summarize medication self-management toolkits for MS, as related to the design, delivery, components, and measures used to evaluate implementation and/or outcomes. Methods: A scoping review was conducted following guidelines by JBI. Articles were included if they focused on adults (18 years or older) with MS. Results: Six articles reporting on four unique toolkits were included. Most toolkits were technology-based, including mobile or online applications, with only one toolkit being paper-based. The toolkits varied in type, frequency, and duration of medication management support. Varying outcomes were also identified, but there were improvements reported in symptom management, medication adherence, decision-making, and quality of life. The six studies were quantitative in design, with no studies exploring the user experience from a qualitative or mixed-methods design. Conclusions: There is limited research on medication self-management toolkits among adults with MS. Future development, implementation, and evaluation mixed-methods research are needed to explore user experiences and overall design of toolkits.